IMPROVEMENT OF AUXILIARY EQUIPMENT ELEKTROPODVIZHNOY OF - , А. І. (Municipal economy of cities. Series: «Economy science», 2013)
The questions of increase of efficiency of work of ancillaries of electric mobile composition are examined. The modernized chart of charging of storage battery is offered with the use of DC-DC of transformer.